Enhancing reading skills in at-risk students: the combined effects of smartphone format, cardiac coherence, positive feedback, and interest-based personalization - Caliari, Peddy (Frontiers in Psychology, 2025)
IntroductionIlliteracy remains a persistent challenge in disadvantaged educational contexts, particularly within Priority Education Network (REP+) schools in Martinique (French West Indies)—a designation in the French educational system for schools located in highly underserved socioeconomic areas requiring additional pedagogical support. This study explores the effects of four pedagogical strategies—smartphone-like formatting, cardiac coherence breathing (an emotional regulation technique), positive feedback, and interest-based text personalization—on reading fluency, comprehension, motivation, and self-esteem in at-risk students.MethodsA total of 120 students from CM1 to 3e participated across four intervention conditions. Data on reading fluency, comprehension, motivation, and self-esteem were collected and analyzed using paired samples t-tests and repeated measures ANOVA.ResultsEach intervention produced significant improvements in one or more outcomes, and all improvements were statistically significant (p < 0.05). Smartphone-like layout improved fluency by 18.5%, enhanced comprehension by 38%, and reduced errors by 48%. Cardiac coherence enhanced comprehension by 35%, reduced errors by 45%, and decreased reading time by 19%. Positive feedback improved self-esteem by 61% and reduced errors by 42%. Personalized texts yielded the strongest effects, improving motivation (+56%), self-esteem (+70%), and comprehension (+54%).ConclusionThe findings highlight the independent value of cognitive, emotional, and motivational levers in literacy interventions for vulnerable learners.